2020
DOI: 10.1111/nph.16823
|View full text |Cite
|
Sign up to set email alerts
|

Towards the flower economics spectrum

Abstract: Understanding how floral traits affect reproduction is key for understanding genetic diversity, speciation, and trait evolution in the face of global changes and pollinator decline. However, there has not yet been a unified framework to characterize the major trade-offs and axes of floral trait variation. Here, we propose the development of a floral economics spectrum (FES) that incorporates the multiple pathways by which floral traits can be shaped by multiple agents of selection acting on multiple flower fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
102
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(104 citation statements)
references
References 87 publications
(126 reference statements)
2
102
0
Order By: Relevance
“…In support, Castro et al ( 2008 ) showed that in Polygala vayredae flower longevity varied in response to the abundance of efficient pollinators indicating that increased longevity might maintain the opportunity for cross-pollination and fertilization in this species when pollinators are scarce. However, there are many factors that can influence flower longevity (Ashman and Schoen, 1994 ; Costa and Machado, 2017 ; Domingos-Melo et al, 2018 ; Roddy et al, 2021 ) and further research is required to establish why non-cross-pollinated flowers of S. umbratica remain open for a much longer time than those of K. virginica .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support, Castro et al ( 2008 ) showed that in Polygala vayredae flower longevity varied in response to the abundance of efficient pollinators indicating that increased longevity might maintain the opportunity for cross-pollination and fertilization in this species when pollinators are scarce. However, there are many factors that can influence flower longevity (Ashman and Schoen, 1994 ; Costa and Machado, 2017 ; Domingos-Melo et al, 2018 ; Roddy et al, 2021 ) and further research is required to establish why non-cross-pollinated flowers of S. umbratica remain open for a much longer time than those of K. virginica .…”
Section: Discussionmentioning
confidence: 99%
“…Flowering plants exhibit high diversity in floral longevity, often reflecting adaptive responses to prevailing ecological conditions, efficient pollinators, and pollen dissemination/receipt (Ashman and Schoen, 1994 ; Castro et al, 2008 ; Roddy et al, 2021 ). The effects of pollination on floral longevity variation have been evaluated in several plant species, showing, for example, that it may be curtailed after pollination to prevent further expenditure on floral resources (Roddy et al, 2021 ) and/or to direct pollinators to non-pollinated flowers (Milet-Pinheiro et al, 2015 ). In contrast, floral longevity may be extended when rain reduces pollen viability, thus increasing the probability of pollinators depositing viable pollen on stigmas and securing high seed set (Domingos-Melo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, traits may have low predictive power (Klimešová, Tackenberg, & Herben, 2016; van der Plas et al, 2020), because there is limited understanding which and how many traits are needed in ecological studies (Shipley et al, 2016). An important step forward has been the grouping of multiple traits into a limited number of syndromes, with continuous variation in the form of gradients of plant strategies (Westoby, Falster, Moles, Vesk, & Wright, 2002; Wright et al, 2004; Chave et al, 2009; Pierce, Brusa, Vagge, & Cerabolini, 2013; Díaz et al, 2016; Klimešová, Martínková, & Herben, 2018; Bergmann et al, 2020; Roddy et al, 2020). For example, Diaz et al (2016) showed that the variation in aboveground traits can be captured by a ‘size’ gradient representing the size of whole plants and plant organs, and an ‘economic’ gradient representing the leaf economics spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of plant functional biogeography have primarily focussed on a few key traits thought to be central to plant strategies, particularly leaf size and specific leaf area, plant height and seed mass (Andrew et al, 2021;Lamanna et al, 2014;Swenson et al, 2012). While such studies have been extremely productive in describing plant ecological strategies across a wide range of environmental conditions, recent attention has been drawn to the overlooked role that flowers and floral traits play in modulating species interactions and shaping patterns of community assembly (E-Vojtkó, de Bello, Durka, Kühn, & Götzenberger, 2020; Roddy et al, 2020). Despite some evidence suggesting that floral traits may have weaker links to macroclimate and landscape patterns than vegetative traits in general (e.g.…”
Section: Main Text: 1 Introductionmentioning
confidence: 99%